Investigating the role of mosquito repellents in atopic dermatitis - Wang, Xiaoxue; Zhu, Zexin (Food and chemical toxicology, 2025)
Mosquito bites are prevalent occurrences among various populations worldwide, mosquito repellent chemical components (MRCCs) have been extensively utilized. MRCCs have been frequently identified in environmental settings nowadays. However, the implications of these compounds on skin conditions, particularly Atopic Dermatitis (AD), are not well understood. In this investigation, we analyzed three commercially available MRCCs: DEET (N,N-diethyl-3-methylbenzamide), IR3535 (ethyl butylacetylaminopropionate), and picaridin (2-(2-hydroxyethyl)-piperidinecarboxylic acid 1-methyl ester). A comprehensive analysis was conducted utilizing various databases to identify potential targets associated with exposure to these MRCCs and their correlation with AD. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses revealed that exposure to these MRCCs influences inflammation-related pathways. Additionally, molecular docking studies indicated significant binding affinities of DEET, IR3535, and picaridin to critical core targets and receptor proteins. Furthermore, a series of cellular assays were conducted to empirically evaluate the actual effects of these three MRCCs on the induction of AD. The results suggest that MRCCs may facilitate the progression of AD by influencing inflammatory processes. This study provides a conceptual framework for understanding the association between MRCCs and the risk of AD, thereby contributing to the formulation of strategies aimed at mitigating their effects on dermatological disorders. •Mosquito repellent chemical components (MRCCs) have been widely employed to prevent mosquito bites.•Currently, MRCCs are frequently identified in various environmental contexts.•MRCCs can trigger skin inflammation through multiple signaling pathways and are associated with the induction of atopic dermatitis (AD).